RELATIONSHIP OF BIORHYTHMS CYCLE WITH COMPUTER BASED TEST (CBT) VALUES IN MEDICAL EDUCATION STUDY PROGRAM STUDENTS AT THE FACULTY OF MEDICINE, SRIWIJAYA UNIVERSITY - Dita, Nurul Salmah Alia; bahar, Erial; Roflin, Eddy (Fakultas Kedokteran Universitas Sriwijaya, 2019)
The human body has many rhythms, one of which is biorhythms. Biorhythms consist of three cycles namely physical, emotional and intellectual cycles. Each cycle has positive, negative and critical phases. When taking an exam, a person needs good physical, mental, and intellectual condition. By using the biorhythms cycle, one can see these conditions in order to prepare for the exam. This research is an observational analytic study with cross sectional design. The sample consisted of 386 students of the Medical Education Study Program of Sriwijaya University in 2014 and 2015 in total sampling that met the inclusion criteria. Data taken in the form of secondary data consisting of CBT scores, exam dates, and entry points obtained from the academic section of the Faculty of Medicine, Sriwijaya University, while data on birth dates, BMI and IQ scores were taken from the questionnaire. Biorhythm cycle data is retrieved using biorhythm software. Data processing was performed using Kruskal Wallis test analysis and Linear Regression. From the results of bivariate analysis with the Kruskall Wallis test it is found that IQ scores have a relationship with CBT values (p = 0.010), university entrance has a relationship with CBT values (p = 0,000), and the physical cycle of biorhythms is related to CBT values (p = 0.011), However, in multivariate analysis (Linear Regression) the physical cycle of biorhythms has no relationship with the value of CBT. There is no correlation between biorhythms cycles and CBT scores in the Medical Education Study Program students at the Faculty of Medicine, Sriwijaya University.